DUGAAN BELUM DIKEMBALIKANNYA BARANG MILIK NEGARA OLEH EKS PEJABAT NEGARA - Reine Rofiana (Universitas 17 Agustus 1945 Samarinda, 2018)
State officials have a mandate from the people to run their positions inaccordance with their duties. In order to perform their duties, stateofficials are given the authority to use state facilities to facilitate theirwork. But what happens if state officials allegedly misuse the state'sfacilities. The crowd's enthusiasm was recently shocked by the news of thealleged not yet returned of the use of state assets by ex state officials.This Assets’ State is intended as a facility for state officials in runningtheir basic daily tasks and functions (instrumental values). If it is indeedtrue that there are state officials who have allegedly not returned theAssets’ State even though their term of office has expired, then this is nolonger in line with its instrumental value because the purpose of usingAssets’ State has deviated from what it should be.This paper is more focused on normative writing that is by reviewing somereferences related to the Assets’ State is connected by legal theories andregulations according to the author's perspective, based on the ethictheory, criminal perspective, etc. The authors suggest that another exofficial state should have awareness so as to prevent similar cases willhappen in the future and for be more sensitive and responsible inmanaging this country.